Thioredoxin Reductase Is Involved in Development and Pathogenicity in Fusarium graminearum - Fan, Xinyue; He, Fang; Ding, Mingyu; Geng, Chao; Chen, Lei; Zou, Shenshen; Liang, Yuancun; Yu, Jinfeng; Dong, Hansong (Frontiers in Microbiology, 2019)
Fusarium graminearum is one of the causal agents of Fusarium head blight and produces the trichothecene mycotoxin, deoxynivalenol (DON). Thioredoxin reductases (TRRs) play critical roles in the recycling of oxidized thioredoxin. However, their functions are not well known in plant pathogenic fungi. In this study, we characterized a TRR orthologue FgTRR in F. graminearum. The FgTRR-GFP fusion protein localized to the cytoplasm. FgTRR gene deletion demonstrated that FgTRR is involved in hyphal growth, conidiation, sexual reproduction, DON production, and virulence. The ∆TRR mutants also exhibited a defect in pigmentation, the expression level of aurofusarin biosynthesis-related genes was significantly decreased in the FgTRR mutant. Furthermore, the ∆TRR mutants were more sensitive to oxidative stress and aggravated apoptosis-like cell death compared with the wild type strain. Taken together, these results indicate that FgTRR is important in development and pathogenicity in F. graminearum.